Corporate governance, pyramid ownership, and firm value: Evidence from Vietnam - Tr?n, Th? H?i Lý (University of Economics Ho Chi Minh City, 2023)
This paper examines the relation among corporate governance practices, pyramid ownership structure, and firm value by using a sample of Vietnamese listed firms. Using a sample of 103 non-financial firms listed on HOSE for the period from 2012 to 2014, and employing two-stage least square regression (2SLS) to deal with potential endogeneity, we find that some indicators, commonly adopted as a key components of corporate governance, such as size or independence of board of directors, are imperfect proxies for corporate governance practices. Our results indicate that it is better to employ a corporate governance index (CGI), including 117 criteria developed by Connelly, Limpaphayom, and Nagarajan (2012) since it allows for more comprehensive estimation of corporate governance. More interestingly, our results show that the pyramid ownership plays an important role in the effect of corporate governance on firm value. The results are consistent regardless of whether companies have high or low family ownership.